Optimizing Work Efficiency by Addressing Operator Fatigue Concerns: Mengoptimalkan Efisiensi Kerja dengan Mengatasi Masalah Kelelahan Operator - Agil, Mochamad Sofwan; Isma Putra, Boy (Universitas Muhammadiyah Sidoarjo, 2024)
The study conducted at PT. Tjiwi Kimia aimed to assess the fatigue criteria and mental load experienced by production operators of cartoon box in the context of the company's 3-shift operation. Using the Bourdon Wiersma method for fatigue evaluation and the NASA TLX method for mental load analysis, findings revealed varying levels of fatigue and mental burden across different shifts. Notably, the morning shift exhibited